PTU-041 Single centre study evaluating a hybrid network solution for an upper gi bleed rota. (17th June 2017) - Yong, KK; Peters, R; Marshall, J; Ellis, A
Abstract : Introduction: The Horton General Hospital (HGH) is a small DGH located 30 miles away from a tertiary endoscopy centre, John Radcliffe Hospital (JRH). Both hospitals are part of Oxford University Hospitals NHS Foundation Trust In October 2015, the endoscopy unit at the HGH closed for 1 year for a refurbishment to maintain JAG compliance. During that time it was possible to provide urgent 'next day' endoscopy for in-patients but not a full 24/7 emergency service. A model of care was devised whereby any patient requiring emergency out-of-hours endoscopy was stabilised and transferred to JRH. This is an observational study to determine the safety of emergency endoscopy service provision using a 'hub and spoke' model between district general and tertiary centre within a single trust. Method: Data was collected prospectively using the Endobase reporting system and electronic patient discharge letter. Patient demographics, reason for referral, endoscopic findings, endoscopic interventions and patient survival were extracted electronically. The endpoints were 24 hour, 7 days, 28 days survival of patients transferred to the JRH prior to receiving endoscopy at the HGH and those transferred to JRH for further endoscopic interventions. Results: During the 1 year observational period, 184 referrals for inpatient urgent or emergency endoscopy were received. The majority of referrals (94%) were managed at HGH on a 'next morning basis.' A total of 11 patients (6%) required transfer to the JRH following initial resuscitation by on-call medical teams (Table 1). Only 4 of these 11 transferred patients required endoscopic treatment to achieve haemostasis. Standard dual therapy techniques were used including adrenaline injection, vessel clipping and heater probe. There were no recorded deaths at 24 hours, 7 days and 28 days for any patient who received resuscitation at the HGH prior to transfer for endoscopy at the JRH. 4 patients (2%) received an initial endoscopy at HGH but later required transfer to JRH for on-going management (Table 2). There were 3 deaths (1.6%) during the study; one 87 year old from an unrelated myocardial infarction following an OGD for a M-W tear, one 72 year old from a perforated duodenal ulcer identified at endoscopy and one 89 year old from an iatrogenic oesophageal perforation managed conservatively due to age and co-morbidities. Conclusion: This one year observational study demonstrates that a safe and effective out of hours 24/7 endoscopy service can be provided using a 'hub and spoke model' of care between district general and tertiary referral centre. With increasing financial and service pressures on emergency services throughout the NHS, we suggest that this model could potentially be adopted more widely to support smaller centres that are not able to provide a full 24/7 endoscopy service. Disclosure of Interest: None Declared